HDO Reaction of THF Using Pt/γ-Al2O3 Catalyst Enriched by Alumina: Effect of Temperature to Product Distribution, Rate of Reaction and Deactivation of Catalyst - Hidayat, Yuniawan; Nurcahyo, Idul Fitri; Sofiana, Ana; Saputro, Arifin Dwi (UNIVERSITAS SEBELAS MARET (UNS), 2014)
Effect of temperature variation to product distribution, rate and deactivation of catalyst of tetrahydrifuran hydrodeoxygenation have been conducted using Pt/gAl2O3 with aluminum enrichmen. Reaction was conducted by flow system. Product of reaction were analyzed as propane (C3) and buthene derivate (C4). At 350ºC, reaction product and rate constant were optimum. At higher temperature, product distribution was shift from C4 to C3. Lowering pore size catalyst, surface area and acidity of catalyst were responsible to catalyst deactivation. Deactivation process was follow exponential regression.